2011
DOI: 10.4236/health.2011.312127
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in the use of delivery care services in Bangladesh: a comparative study between 2004 and 2007

Abstract: The study explores inequalities in the utilization of delivery care services in different administrative divisions in Bangladesh, by key socioeconomic factors. It estimates the extent of the relationship between women’s socioeconomic inequalities and their place of delivery during 2004 and 2007. Trends in relation to place of delivery in relation to residency and education over a period of thirteen years (1993-2007) have also been measured. The study analyzed the trends and patterns in utilization of instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
6
13
1
Order By: Relevance
“…This is in line with the findings of previous studies that revealed distributions in general health care that favoured the rich [18,27]. Similarly, pro-rich distributions have been reported in studies from other developing countries [6,7,39]. …”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the findings of previous studies that revealed distributions in general health care that favoured the rich [18,27]. Similarly, pro-rich distributions have been reported in studies from other developing countries [6,7,39]. …”
Section: Discussionsupporting
confidence: 92%
“…Analysis of trend and pattern of institutional delivery in Bangladesh from 1993 to 2007 in relation to residency and education also revealed low utilisation of health facility among women in rural settings [33]. On the contrary, a Nigerian study [34] noted that most urban dwellers deliver at home. This disparity might be attributable to variation in other factors prevailing in these two different study areas such as attitude of healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Public health policies may have contributed to this decline; for more than one decade, Bangladesh has adopted a health, nutrition, and population sector program with defined national strategies for reducing maternal mortality, focusing especially on early detection and appropriate referral of complications, and improvement of quality of care [ 11 , 13 - 15 ]. In spite of overall progress made in the maternal health sector, evidence suggests that there are pronounced social gradients in utilization of key maternal care services and maternal health outcomes in Bangladesh [ 14 , 16 , 17 ]. There are, in fact, huge geographic and socioeconomic inequalities in access to maternal health services across the country [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also critical for targeting interventions to those areas and population subgroups in greatest need. To date, a number of studies have examined utilization of maternal care in Bangladesh [ 11 , 14 , 17 , 20 ]. However, the previous works did not provide a detailed account of social inequalities in the utilization of maternal care across different regions and socioeconomic groups.…”
Section: Introductionmentioning
confidence: 99%